2007
DOI: 10.1007/s00253-007-1178-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of technological options and economical feasibility for cyanophycin biopolymer and high-value amino acid production

Abstract: Major transitions can be expected within the next few decades aiming at the reduction of pollution and global warming and at energy saving measures. For these purposes, new sustainable biorefinery concepts will be needed that will replace the traditional mineral oil-based synthesis of specialty and bulk chemicals. An important group of these chemicals are those that comprise N-functionalities. Many plant components contained in biomass rest or waste stream fractions contain these N-functionalities in proteins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
62
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 39 publications
0
62
0
Order By: Relevance
“…Synthesis of these forms of CGP became possible because the amino acids mentioned also possess a certain affinity for the cyanophycin synthetase CphA (EC 6.3.2.29 and EC 6.3.2.30). This increases the possible applications of CGP or its dipeptides (9, 10) and allows the production of novel bulk chemicals (11,12,13).Recently, it became evident, that in most studies aiming at the incorporation of large fractions of the alternative constituents into CGP, these compounds were found in a soluble form of CGP, while the insoluble form contained only small amounts of the constituents. Steinle et al (7), for example, synthesized soluble CGP with a citrulline content of over 20 mol%, while the corresponding insoluble form contained citrulline only at a fraction of about 5 mol%.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Synthesis of these forms of CGP became possible because the amino acids mentioned also possess a certain affinity for the cyanophycin synthetase CphA (EC 6.3.2.29 and EC 6.3.2.30). This increases the possible applications of CGP or its dipeptides (9, 10) and allows the production of novel bulk chemicals (11,12,13).Recently, it became evident, that in most studies aiming at the incorporation of large fractions of the alternative constituents into CGP, these compounds were found in a soluble form of CGP, while the insoluble form contained only small amounts of the constituents. Steinle et al (7), for example, synthesized soluble CGP with a citrulline content of over 20 mol%, while the corresponding insoluble form contained citrulline only at a fraction of about 5 mol%.…”
mentioning
confidence: 99%
“…Synthesis of these forms of CGP became possible because the amino acids mentioned also possess a certain affinity for the cyanophycin synthetase CphA (EC 6.3.2.29 and EC 6.3.2.30). This increases the possible applications of CGP or its dipeptides (9, 10) and allows the production of novel bulk chemicals (11,12,13).…”
mentioning
confidence: 99%
“…The latter is produced by the industry as a substitute for nonbiodegradable polyacrylic acid, which is used for many technical and medical applications. Thus, composition and structure make this biopolymer interesting for industry (28,41).…”
mentioning
confidence: 99%
“…Recently, several putative applications for CGP and its derivatives have become available, indicating there is a need for its efficient biotechnological production (36,42,43). For the production of CGP at a technical scale, cyanobacteria were shown to be unsuitable due to their low cell densities and polymer contents (3.5% [wt/wt]) and slow growth and circumstantial growth conditions in a photobioreactor (18,19).…”
mentioning
confidence: 99%
“…A detailed study of the solubility behavior of CGP isolated from recombinant E. coli in inorganic salts has been carried out by Füser and Steinbüchel (16). It was shown that the occurrence of the soluble form was not dependent on the origin of cphA or on the host.Recently, several putative applications for CGP and its derivatives have become available, indicating there is a need for its efficient biotechnological production (36,42,43). For the production of CGP at a technical scale, cyanobacteria were shown to be unsuitable due to their low cell densities and polymer contents (3.5% [wt/wt]) and slow growth and circumstantial growth conditions in a photobioreactor (18,19 Also, in the industrially relevant bacteria Pseudomonas putida, Ralstonia eutropha, and Corynebacterium glutamicum, considerable amounts of CGP could be produced after heterologous expression of cphA (3,13,48,49).…”
mentioning
confidence: 99%